Impact of Government Expenditure on Education, Social Protection, Public Services, Infrastructure, Community Empowerment, Investment, and HDI on Economic Growth in Indonesia's 3T Regions - Wardani Pulungan, Rafika; Rahmanta, Rahmanta; Afifuddin Sembiring, Sya'ad (Lafadz Jaya Publisher, 2024)
This research aims to determine the influence of government spending in the fields of education, social protection, public services, infrastructure, community empowerment, investment, and the Human Development Index (HDI) on economic growth in Indonesia's 3T (Disadvantaged, Frontier, Outermost) regions. This study employs quantitative research methods, with a population and sample comprising 62 regions designated as 3T in Indonesia. Data analysis was conducted using panel data regression analysis with the EViews 10 software. The results reveal that government spending on education (BFPEND), public services (BFPU), and community empowerment (BDPM) does not significantly influence economic growth. However, government expenditures on social protection (BFPS) negatively and significantly affect economic growth, while spending on infrastructure (BFINF) and investment (INVEST) positively and significantly impact economic growth. Additionally, the HDI has a negative and significant effect on economic growth. Collectively, government spending across these sectors, along with HDI, has a positive and significant effect on economic growth in Indonesia's 3T regions. A comparison of the average HDI in Disadvantaged Regions versus Frontier and Outermost Regions in Indonesia is also presented.